Uncovering dynamic behaviors underlying experimental oil–water two-phase flow based on dynamic segmentation algorithm - Gao, Zhong-Ke; Jin, Ning-De (Physica A, 2013)
Characterizing complex dynamic behaviors arising from various inclined oil–water two-phase flow patterns is a challenging problem in the fields of nonlinear dynamics and fluid mechanics. We systematically carried out inclined oil–water two-phase flow experiments for measuring the time series conductance fluctuating signals of different flow patterns. We using the dynamic segmentation algorithm incorporating with phase space reconstruction analyze the measured experimental signals to uncover the dynamic behaviors underlying different flow patterns. Specifically, given a time series from a two-phase flow, we move a sliding pointer over the time series and for each position of the pointer we calculate the dynamic difference measure of the phase space orbits generated from the segment to the left and to the right of the pointer. A number of experimental signals under different flow conditions are investigated in order to reveal the dynamical characteristics of inclined oil–water flows. The results indicate that the heterogeneity of dynamic difference measure series is sensitive to the transition among different flow patterns and the standard deviation of dynamic difference measure series can yield quantitative insights into the nonlinear dynamics of the two-phase flow. These properties render the dynamic segmentation algorithm-based approach particularly useful for uncovering the dynamic behaviors of inclined oil–water two-phase flows. ► We use dynamic segmentation algorithm to uncover the dynamic flow behavior. ► We extract statistic associated with chaotic dynamics from experimental signals. ► The statistic is sensitive to the transition among different oil–water flow patterns. ► Our method can yield quantitative insights into the dynamic behavior of flow patterns. ► Broader applicability of our method is demonstrated and articulated.